Combined family-based association and linkage analyses in families affected by attention-deficit hyperactivity disorder - Cristina M. Justice; Kwangmi Ahn; Benjamin Jung; Luke J. Norman; Gustavo Sudre; Wendy Sharp; Marine Bouyssi-Kobar; Saadia Choudhury; Stevi Gligorovic; Paul Kundzicz; Maria T. Acosta; Philip Shaw (Human Genetics, 2026)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent and heritable of neurodevelopmental disorders. To characterize the genetic variants contributing to this heritability, we studied families with members affected by ADHD. Genome-wide array data were obtained on two cohorts: NHGRI Family Cohort (359 nuclear families,1538 individuals) and NCR Family Cohort (25 multigenerational and 132 nuclear families, 631 members). A meta-analysis of family-based association tests (FBAT) of the two cohorts identified three genome-wide significant associations, one upstream from TFRC , and two that were intronic to GSDME and to TRIM31 , with the last gene previously implicated in ADHD. Genes associated with ADHD (MAGMA, gene-based association P < 0.05) overlapped with genes implicated in ADHD by prior case/control genome-wide association studies. Meta-analyses of the linkage signals identified one significant linkage region (LOD > 3) on 19p13.2-13.11 that encompassed a genome-wide significant variant in the FBAT of the NHGRI Family Cohort (rs55741253, P = 2.68 × 10 − 8 ). Additionally, two of the five linkage regions that reached a LOD > 2 in our meta-analysis replicated significant linkages from prior studies (prior studies reporting 13 linkages with LOD > 3.0; hypergeometric test of overlapping linkage signals, P < 0.01). Using neuroimaging data from the NCR cohort, we found genes associated with ADHD overlapped with genes associated with the brain’s total surface area and a feature of functional connectivity, reflecting the interaction between the brain’s default mode and task positive networks. Such work begins to delineate the neural substrates of the discovered genetic associations with familial ADHD.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pharmacological evidence that 5-HT2C receptor blockade selectively improves decision making when rewards are paired with audiovisual cues in a rat gambling task - Wendy K. Adams; Chris Barkus; Jacqueline-Marie N. Ferland; Trevor Sharp; Catharine A. Winstanley (Psychopharmacology, 2017)

Estimates of recharge in two arid basin aquifers: a model of spatially variable net infiltration and its implications (Red Light Draw and Eagle Flats, Texas, USA) - Wendy Marie Robertson; John M. Sharp (Hydrogeology Journal, 2013)